Negotiating Homosexuality in Islam : A Legal-hermeneutical Examination of Modern Shīʿī Discourse - Alipour, Mehrdads, (Middle East and Islamic Studies E-Books Online, Collection 2024., 2024)
To enrich the existing debates on Islam and sexual diversity, in the present book, I seek the potential discursive spaces on homosexuality in modern Imāmī legal debates. I have undertaken this research on the thesis that modern Imāmī legal tradition on homosexuality is more flexible and dynamic than one might expect. To address this essential issue, I build the study around the following constructive question: what are the discursive spaces on homosexuality in contemporary reflections within modern Shiʿi legal scholarship? Responding to this central query, the study is premised on the notion that Imāmī legal sources consist of a tradition of sacred (textual) sources, intellectual reasoning, a vast stockpile of (often contrasting) interpretations of these sources, and a distinguished methodological repertoire called ijtihad . Following the same methodology, in this work, I describe, analyse, and critique such textual-exegetical and intellectual-rational discursive aspects concerning homosexuality.